A. (−3, 3)
<span>3x – 4y = 21
</span>3(-3) - 4(3) = 21
-21 = 21 >>>>> not equal
B. (−1, −6)
<span>3(-1) - 4(-6) = 21
</span>21 = 21 >>>>>>>>>>Equal
C. (7, 0)
<span>3(7) - 4(0) = 21
</span>21 = 21>>>>>>>>>>equal
D. (11, 3)
<span>3(11) - 4(3) = 21
</span>21 = 21 >>>>>>>>>equal
Answer:
D. Pythagorean
Step-by-step explanation:
Given the identity
cos²x - sin²x = 2 cos²x - 1.
To show that the identity is true, we need to show that the left hand side is equal to right hand side or vice versa.
Starting from the left hand side
cos²x - sin²x ... 1
According to Pythagoras theorem, we know that x²+y² = r² in a right angled triangle. Coverting this to polar form, we have:
x = rcostheta
y = rsintheta
Substituting into the Pythagoras firnuka we have
(rcostheta)²+(rsintheta)² = r²
r²cos²theta+r²sin²theta = r²
r²(cos²theta+sin²theta) = r²
(cos²theta+sin²theta) = 1
sin²theta = 1 - cos²theta
sin²x = 1-cos²x ... 2
Substituting equation 2 into 1 we have;
= cos²x-(1-cos²x)
= cos²x-1+cos²x
= 2cos²x-1 (RHS)
This shows that cos²x -sin²x = 2cos²x-1 with the aid of PYTHAGORAS THEOREM
Answer:
n + 11 and 11 + n
Step-by-step explanation:
Let n be the unknown number,
n is increased by 11,
That is, n + 11
By the commutative property of addition,
The expression would be,
11 + n
For drawing a model that shows n + 11
Take two boxes in which first shows n and second shows 11 and add them,
Similarly, for showing 11 + n, take first box that shows 11 and second box that shows n then add them.
Answer:
420
Step-by-step explanation:
Answer:
a = b + k + u
Step-by-step explanation:
hope this helps